The effects of PPnanoclay loading on the mechanical properties of polypropylene-clay nanocomposites / Anizah Kalam and Mohamad Nor Berhan - Kalam, Anizah; Nor Berhan, Mohamad (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2009)
This paper deals with the use of polypropylene-nanoclay (PPnanoclay) which is a masterbatch type of nanocomposite. The PPnanoclay was mixed with polypropylene to form Polypropylene-clay nanocomposite. Mechanical tests such as tensile, flexural and impact tests were performed to determine the mechanical properties of the composites. The PPnanoclay content was also varied at 10phr, 25phr, 40phrand 100 phr to study its effects on the mechanical properties. The experimental results indicate that the addition of PPnanoclay has increased the tensile modulus and tensile strength to 27% and 5% respectively. The enhancement of flexural properties was also obtained with the addition of PPnanoclay in Polypropylene. The incorporation of PPnanoclay in polypropylene has resulted in the reduction of elongation at breaks and impact resistance. Generally, the elongation at break was found to be highly affected by the addition of PPnanoclay into the polypropylene. This study also revealed that the optimum PPnanoclay loading is at 25 phr, which showed the highest tensile and flexural properties. The Scanning Electron Microscope (SEM) observation also confirmed that the addition of PPnanoclay into polypropylene has decreased the ductility of polypropylene and continues to decrease with the increasing amount of PPnanoclay content.